Penggunaan Media Sosial di Kalangan Wanita Dewasa Ditinjau dari Nilai-Nilai Karakter - Nenden Elista Fauziatunisa (UIN Siber Syekh Nurjati Cirebon, 2021)
The purpose of this research is to analyze and find out the dynamics of the use of social media among adult women in the formation of character values, this is both seen from the pros and cons of advances in communication technology among adult women seen from the character values, where in the present social media has it is no stranger to every circle, be it teenagers, adults or even the elderly. The research method used a qualitative approach and also Library Research. Data collection was carried out by observation, in-depth interviews with adult women of UIN SUKA postgraduate students who actively use social media. The results of the study found that social media is determined by several applications, content, and also the effect it causes in shaping the character of women. Social media in particular has a close relationship in shaping values and also personal character. Social media also reflects that the positive impact of technological advances in education is able to create good learning activities, make it easier for students to find learning resources, and with technology can help students learn to apply technology in the teaching and learning process, so that students are more interested in learning. The findings also show that the negative impact of technological development, one of which is the low character value, especially from the social aspect, and the lack of communication between students and their surroundings. Consumptive, and also tend to be ignorant of the surrounding environment.